Encouraging Student Question-Asking in Primary Classrooms: Teachers’ Strategies, Behaviors, and Assessment Techniques - Arviana, Nerisha (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This qualitative study explores the strategies, assessment techniques, and classroom behaviors that primary school teachers employ to encourage student question-asking, a critical component of active and meaningful learning. Drawing on semi-structured interviews with nine classroom teachers selected via purposive sampling, the study adopts a phenomenological approach to understand how educators foster inquiry in their daily practices. The findings reveal ten key themes that reflect teacher efforts to promote question-asking, including encouraging active participation, addressing diverse learning styles, enabling students to formulate their own questions, and overcoming student shyness. Teachers reported using visual aids, storytelling, group discussions, drama, peer questioning, and feedback techniques tailored to individual learners. Additionally, teacher behaviors—such as verbal encouragement, maintaining eye contact, and empathetic listening—were found to cultivate supportive learning environments conducive to curiosity and self-expression. The study concludes that student questioning is influenced by the alignment of instructional strategies with students’ cognitive and affective needs. It recommends sustained professional development focused on inquiry-based pedagogy to expand students’ questioning capacities and support the formation of democratic, student-centered classrooms.